2023
DOI: 10.1002/adsc.202300502
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Halogen‐ and Chalcogen‐Bonding Organocatalyst

Abstract: Applications of both halogen and chalcogen bonding in organocatalysis are by now well established with various examples. However, the combination of both interactions within one catalyst is currently unknown. Herein, we describe the synthesis of such a mixed chalcogen‐ and halogen‐bond donor and present a first indication of its catalytic activity in a benchmark reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Very recently, Huber reported a mixed catalyst 5‐Te,I combining tellurium and iodine as the ChB and XB donor centres, respectively. In this unsymmetrical structure, tellurium was carried by a triazolium unit such as in catalysts 2‐Te 2 (Scheme 2A) and iodine was placed on a benzimidazolium heterocycle [50] . The synthesis of 5‐Te,I was performed in several steps from benzimidazole 15 (Scheme 6A).…”
Section: Catalysis With Tellurium Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Huber reported a mixed catalyst 5‐Te,I combining tellurium and iodine as the ChB and XB donor centres, respectively. In this unsymmetrical structure, tellurium was carried by a triazolium unit such as in catalysts 2‐Te 2 (Scheme 2A) and iodine was placed on a benzimidazolium heterocycle [50] . The synthesis of 5‐Te,I was performed in several steps from benzimidazole 15 (Scheme 6A).…”
Section: Catalysis With Tellurium Derivativesmentioning
confidence: 99%
“…In this unsymmetrical structure, tellurium was carried by a triazolium unit such as in catalysts 2-Te 2 (Scheme 2A) and iodine was placed on a benzimidazolium heterocycle. [50] The synthesis of 5-Te,I was performed in several steps from benzimidazole 15 (Scheme 6A). After a Sonogashira reaction with trimethylsilylacetylene, iodination of the benzimidazole was realized by deprotonation and I 2 quenching to give 16 in good yield.…”
Section: Bis-triazolium Tellurium Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in early works, some catalytic effect was observed for noncharged XB and ChB donors, , the cationic σ-hole donors exhibit a significantly higher catalytic activity (Figure ). For XB donors, it has been demonstrated that iodoazoliums and iodopyridiniums featuring an exocyclic iodine­(I) center effectively catalyze an extensive series of organic transformations, whereas hypervalent iodine­(III) species (iodonium salts) possess even a greater catalytic activity than the iodine­(I) derivatives. For ChB donors, recent publications unambiguously indicate that telluronium salts (R 3 Ch + X – , Ch = Te IV ) exhibit a significantly higher Lewis acidity compared to the tellurium­(II) derivatives and lighter chalcogen­(IV)-derived species, whereas selenonium salts (Ch = Se IV ) have a higher , or comparable catalytic activity than their sulfonium analogues (Ch = S IV ), which, in turn, exhibit a sufficient catalytic activity toward a series of model organic transformations. , …”
Section: Introductionmentioning
confidence: 99%
“…This is due to its unique chalcogen bonding ability, thus enabling the activation of small yet highly relevant organic substrates. For example, Huber and co-authors recently designed a Te-based catalyst in an indole Michael addition reaction [1][2][3][4][5]. Pale and Mamane utilized another Te-based catalyst in an electrophilic bromine-mediated cyclization reaction [6,7], and Gabbaï yet another in a different cyclization reaction [8,9], among other catalytic chalcogen bonding activation examples [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%